2022
DOI: 10.1002/brb3.2665
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dexmedetomidine on postoperative cognitive dysfunction in the elderly: A meta‐analysis of randomized controlled trials

Abstract: Introduction Dexmedetomidine (Dex) is suggested to be neuroprotective. However, influence of Dex on postoperative cognitive dysfunction (POCD) in the elderly remains unknown. Methods We performed a meta‐analysis of randomized controlled trials (RCTs) to evaluate the effect of Dex on POCD. Relevant studies were obtained by search of PubMed, Embase, and Cochrane's Library databases. A random‐effect model was used to pool the results. Results Fourteen RCTs including 1626 adults of 60 years or older who received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Perioperative administration of Dex also significantly improves early postoperative cognitive function in children undergoing tonsillectomy (Peng et al, 2021). Studies have found that Dex injection during laparoscopic cholecystectomy reduces serum proinflammatory cytokines and the occurrence of POCD (Wu et al, 2022; Yu et al, 2022). Dex was shown to reduce the severity of neuroinflammation and neuronal apoptosis in animal models of systemic inflammatory response syndrome (SIRS) and surgical injury (Du et al, 2021; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative administration of Dex also significantly improves early postoperative cognitive function in children undergoing tonsillectomy (Peng et al, 2021). Studies have found that Dex injection during laparoscopic cholecystectomy reduces serum proinflammatory cytokines and the occurrence of POCD (Wu et al, 2022; Yu et al, 2022). Dex was shown to reduce the severity of neuroinflammation and neuronal apoptosis in animal models of systemic inflammatory response syndrome (SIRS) and surgical injury (Du et al, 2021; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[18] Although it has limitations such as learning effect and capping effect, it is easy to be carried out in a short time with high-sensitivity and specificity for the diagnosis of POCD, which has already been widely applied in clinical practice. [19] POCD occurred after surgery with incidence ranging from 17% to 56% and with a tendency to resolve over time from 3% to 34.2%. [20] In the present study, elderly patients with esophageal cancer were included as research objects, and the incidence of POCD detected by MMSE scale revealed to be 23.1%, which was also consistent with previous research results.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses published in 2019 [44] and 2022 [45] were conducted to investigate the impact of DEX on postoperative neurocognitive function of elderly patients who underwent non-cardiac surgery. Regarding the elderly patients who had non-cardiac surgery, both studies found that DEX administration during the perioperative period was more effective than other sedatives in maintaining cognitive function after the surgical intervention.…”
Section: Discussionmentioning
confidence: 99%